1991 Novel & Short Story Writer's Market (Writer's digest books, 1990)
This book shows you WHERE and HOW to sell what you write with: 1,900 listings of fiction publishing opportunities, all completely updated for 1991-including commercial periodicals, book publishers, small presses, and literary/small circulation magazines - to help you target the right markets for your work, detailed information on contact names, addresses, pay rates, submission requirements, and helpful tips from the editors so you make sure your work ends up in the right people's hands, 10 chapters of original, "how-to" fiction writing and marketing instruction, featuring articles on the craft and technique of novel and short story writing answering the questions 'you' want the answers to and a guide to contests, grants, fellowships, and awards to help you make valuable contacts in the industry. With additional special interviews, list of literary agents and detailed category index of markets listed according to subject interests, to assist you in achieving publication easily and quickly.